The Influence of Implementation of Total Quality Management, Competence of Medical Personnel, Work Culture and Digital Transformation on Organizational Performance through Competitive Advantage as Moderating Variables at Santo Antonio Hospital - Tiara Innotata; Puput oktamianti; Oka Wilsen Joung (Budapest International Research and Critics University, 2022)
The purpose of this research is the effect of the implementation of total quality management, the competence of medical personnel, and digital transformation on organizational performance with competitive advantage moderation. Total quality management has a significant negative effect on competitive advantage. The competence of medical personnel has a significant positive effect on organizational performance. The competence of medical personnel has a significant positive effect on competitive advantage. Digital transformation has a significant positive effect on competitive advantage. Work culture has a significant positive effect on organizational performance. Work culture has a significant positive effect on competitive advantage. Competitive advantage has a significant positive effect on organizational performance. Total quality management mediated by competitive advantage significantly positively affects organizational performance. The competence of medical personnel mediated by competitive advantage significantly positively affects organizational performance. Digital transformation mediated by competitive advantage significantly positively affects organizational performance. Competitive advantage can mediate work culture's relationship to organizational performance. Hospitals need to improve TQM to improve service quality and compete well.